2019
DOI: 10.1186/s12909-018-1439-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional comparison of spiral versus block integrated curriculums in preparing medical students to diagnose and manage concussions

Abstract: BackgroundAn integrated curriculum is designed to be repetitive yet progressive and the concept has rapidly established itself within medical education. National organizations have recommended a shift to a spiral curriculum design, which uses both vertical and horizontal integration. This study examined differences between the recently implemented integrated spiral (class of 2019) and conventional block (classes of 2016–2018) MD curricula at the University of British Columbia (UBC) with respect to knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
2
13
0
6
Order By: Relevance
“…(Arantes, Andrade, Barbosa, & Ferreira, 2020) The findings of our study are also supported by the work of Sarah Fraser et al who reported a strong understanding of knowledge resulting from the integrated teaching. (Fraser et al, 2019)Munazza Asad reported that multiple strategies employed in an integrated curriculum help enhance concept making in the students which supports the findings of this research. (Asad & Khaliq, 2020) As Ambreen Gul et al reported in their article that innovative teaching strategies like CBL, are an effective means to learn and consolidate concepts for students in the pre-clinical years and these findings support the assertions made in our study.…”
Section: Students Perception Of the Importance Of Disciplinesupporting
confidence: 82%
See 1 more Smart Citation
“…(Arantes, Andrade, Barbosa, & Ferreira, 2020) The findings of our study are also supported by the work of Sarah Fraser et al who reported a strong understanding of knowledge resulting from the integrated teaching. (Fraser et al, 2019)Munazza Asad reported that multiple strategies employed in an integrated curriculum help enhance concept making in the students which supports the findings of this research. (Asad & Khaliq, 2020) As Ambreen Gul et al reported in their article that innovative teaching strategies like CBL, are an effective means to learn and consolidate concepts for students in the pre-clinical years and these findings support the assertions made in our study.…”
Section: Students Perception Of the Importance Of Disciplinesupporting
confidence: 82%
“…(Zhao et al, 2020) The integrated curriculum promotes a strong understanding and retention of knowledge as reported by Sarah Fraser et al and this is in agreement with the findings of our study. (Fraser, Wright, van Donkelaar, & Smirl, 2019) The study finding also parallels the assertions made that breaking down the boundaries between basic and clinical sciences would improve retentions. (Brauer & Ferguson, 2015) Conceptual knowledge of students: Our study found that conceptual knowledge of the students has improved since the introduction of integration.…”
Section: Students Perception Of the Importance Of Disciplinesupporting
confidence: 75%
“…Three of the seven papers forming this scoping review gave details about the amount of time assigned for concussion teaching [ 3 , 21 , 22 ]. In 2012, Burke et al [ 21 ] found that Canadian universities on average dedicated a little over 30 min of formal concussion teaching to their undergraduates, and just over 90 min of general head injury teaching with a concussion component.…”
Section: Resultsmentioning
confidence: 99%
“…Along with the traditional "module" system, in which preclinical subjects are integrated into in system-based courses, the "spiral model" is gaining more and more popularity, in which there is horizontal and vertical integration, and revision of the material studied previously at a higher level [13,15,34].…”
Section: Integrated Program Optionsmentioning
confidence: 99%
“…Thus, graduates of medical universities who had adopted an integrated program were better prepared to meet the needs of the society they were supposed to serve to. The integrated curriculum was recognized as the best way to build up competencies, and it received a great support of the national accreditation agencies [6,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%